The effect of aluminum treatment on metabolism in oil palm seedlings (Bioscience Journal, 2023)
Due to rainfall and high temperatures, the Amazonian soil undergoes changes in its source material and leaching of base cations. This results in deep, infertile, and acidic soil. Aluminum present in acidic soil impairs plant growth and development by inhibiting root formation, enzymatic reactions, absorption, transport, and nutrient utilization. This study aimed to evaluate the effects of aluminum dosage on the metabolism of the oil palm Elaeis guineensis Jacq. The study was conducted in a greenhouse at the Federal Rural University of Amazonia. The experimental design was randomized, with five replications, in which dosages of 0, 10, 20, 30, and 40 mg L-1 aluminum chloride (AlCl3.6H2O) were administered. Electrolyte leakage, nitrate, nitrate reductase, free ammonium, soluble amino acids, proline content, and soluble proteins were analyzed in the leaves and roots of the oil palm. The highest concentration of aluminum was found in the roots. AlCl3 treatment at 40 mg L-1 increased electrolyte leakage, nitrate, ammonium, and proline concentrations in the roots, and amino acid concentrations in both the leaves and roots. Furthermore, a decrease in nitrate reductase enzyme activity was observed in the roots. This study demonstrates that the oil palm has mechanisms of tolerance to aluminum toxicity.